The Buried Lagoon and the Invisible Rivers: Images of Mexico City’s Water in José Emilio Pacheco’s Poetry - di Biase Castro, Elisa T. (Ángulo Recto. Revista de estudios sobre la ciudad como espacio plural, 2013)
The buried waters of Mexico City, its now invisible rivers and the watery city it once was –which reminded the Spanish conquerors the image of Venice–, seem to underlie the modern metropolis and to resurge as phantoms. The water, buried alive, haunts José Emilio Pacheco with its nostalgic and terrifying presence. The life and literary work of this author are closely tied to the city where he was born. At the same time, these waters, with their eternal remaining, symbolize for the author, obsessed with the theme of tempus irreparabile fugit, the endless cycle of life that saves the city from passing and imminent destruction; the process which takes it to be constantly reborn, endlessly reflected on the images of its founding myths as if those resided in the uterus of the disappeared waters.